Evans Syndrome Associated with Pregnancy and COVID-19 Infection - Gayathri Vadlamudi; Leah Hong; Madhurima Keerthy (Case Reports in Obstetrics and Gynecology)
Background. Evans syndrome (ES) is a chronic autoimmune disease characterized by autoimmune hemolytic anemia along with immune thrombocytopenic purpura. Few case reports of ES in pregnancy have been published, and ES may be difficult to distinguish from other diagnoses more common in pregnancy. Guidelines for treatment of ES are not well-defined. Case. A 23-year-old multigravid woman in active labor was found to have severe anemia and thrombocytopenia. She was diagnosed with ES and started on immunosuppressive treatments for persistent immune thrombocytopenic purpura. In the postpartum period, she was found to have coronavirus (COVID-19) infection and acute pulmonary embolism. Conclusion. Evans syndrome is a challenge to diagnose in pregnancy and poses important considerations for intrapartum and postpartum management.